Debugging mixed-signals circuits via IEEE1149.4 – a built-in mixed condition detector - Felgueiras, Manuel C. (2017)
Diagnosing design faults in a mixed-signals circuit is no trivial task, due to the inherent uncertainties associated with analog signals, not mentioning the interaction between the analog part and the digital part. Using debug and test tools is one way to deal with the problem, especially during the prototyping phase, however if a physical access is required then the same restrictions that led to other solutions, based on electronic access, apply. This is particularly the case that led to the emergence and wide acceptance of the IEEE1149 family of test infrastructures, which relies on an electronic test access port. While the IEEE1149.4 test infrastructure enables the structural and parametric test of mixed-signal boards, its use is still far from reaching a wide acceptance, namely due to the lack of alternative applications, such as debugging, as seen in the 1149.1 domain of purely digital circuits. Building upon the rationale that enabled transferring the structural test of board interconnections between analog pins, from the analog domain to the digital domain, using the mechanisms present in an Analog Boundary Module, as defined in the IEEE1149.4 Std., we propose a new way to support debug operations in 1149.4 mixed-signals circuits. In particular, we describe a built-in mechanism able to detect both internal and pin-level mixed-signal conditions, and hence able to support watchpoint/breakpoint operations at the IC level.